Impact of Culture on Entrepreneur Intention - Syed Imran Sajjad; Aasim Munir Dad . (Information Management and Business Review, 2012)
The main purpose of this study is to identify the role of entrepreneurship in Pakistan. After reviewing the literature, researchers identify those predictors who influence the entrepreneur’s intention with the help of socio cognitive model. National culture of a country influences the entrepreneur’s intention to start new business. Perceived feasibility, perceived desirability and entrepreneurs experience has a direct impact on entrepreneur’s intention. The study finds out the impact of culture on entrepreneur intention, different cultures have different ways to influence the entrepreneur intention and different ways to impact on intentions towards perceived feasibility and perceived desirability .The study helps entrepreneur’s decision making process and also helps out the development of further new business in Pakistan, motivates students to become entrepreneurs and analyzes their feasibility and desirability. Culture varies from country to country, within country different provinces, how different cultures, different traditions, norms and values. So in future, it helps to analyze entrepreneur’s intention in different cultures.